PENGARUH MOTIVASI, KEMAMPUAN DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN MEUBLE BASUKI LACASA ART GALLERY SINGOSARI-MALANG - Yuliana, Rachma; Khirom, Novita Rifatul (Magister Manajemen Universitas Wisnuwardhana, 2020)
The role of human resources in the organization is very important, because it is natural if the management give more attention through the policies that has been taken. Currently many problems that arise related to employment, especially employee performance, therefore the problems relating to performance need to be resolved. Motivation is a condition or energy that moves employees directed to achieve the goals of the company organization. besides motivation, another thing that can affect performance is ability, by having the appropriate ability in the field of work that he does, then he can work better. While employee performance in general is influenced by two main factors, namely the ability and driving force or what is called motivation. The purpose of this study were: 1) describing the motivation, work ability, commitment and performance employers at the Meuble Basuki Lacasa Art Gallery Singosari-Malang. 2) analayzing the influences of motivation, work ability, and commitment employer performance at the Meuble Basuki Lacasa Art Gallery Singosari-Malang Company. And 3) analyzing the dominant influences of Motivation, Ability and Work Commitment on Employee Performance at Singosari-Malang Meuble Basuki Lacasa Art Gallery. The analysis method used in this research was descriptive analysis. The results of his research were: 1) Motivation, work ability and commitment of employer simultaneously have a significant effect on the performance of employer at Meuble Basuki Lacasa Art Gallery Singosari Malang, and 2) Based on the results of the t test shown that motivation, work ability and employee commitment simultaneously have a significant effect on employee performance at Meuble Basuki Lacasa Art Gallery Singosari Malang, while the variable that has a dominant influence on employee performance were motivation. Key Word : Motivation, Work Ability, Komitmen dan Commitment of Employer